The neurologists: A history of a medical specialty in modern Britain, c.17892000. - Casper, Stephen T. (Manchester Univ Press, 2014)
Describes how Victorian physicians located in a medical culture that privileged general knowledge over narrow specialism came to be transformed into the specialised physicians we now call neurologists.